A comparison of singles and doubles badminton: heart rate response, player profiles and game characteristics - Alcock, A.; Cable, N. T. (International Journal of Performance Analysis in Sport, 2009)
Physiological demands of singles and doubles badminton were compared to assist coaches in evidence-based design of training programs. Sixteen male players (eight singles and eight doubles) were tested for physical and physiological characteristics. Heart rates were monitored during competition and games videoed to allow for lapsed-time analysis. Mean and peak heart rates were significantly greater in singles (88.8% and 96.8% of maximal heart rate respectively) than doubles (75.5% and 89.0%). Singles players took more steps per game (593.8 vs 314.5) and at a higher velocity. There were no differences in rally or game length. Singles players had greater predicted VO2max (50.6 vs 45.5 ml·kg-1 ·min-1) and flexibility, and lower body fat levels (15.5% vs 21.9%). There were no differences in power, speed or agility. Game analyses showed tactical differences, with 89.6% of shots in singles played to the extreme fore- and rear-court (clear, drop, lift or net shot) or a smash, and doubles involving a greater diversity of shots. Success in badminton may require focusing on specific discipline strategies. For example, singles training drills could focus on efficient movement about the court and doubles on a faster, more attacking game.